You know her - Jennett, Meagan, 1989- (MCD, Farrar, Straus and Giroux, 2023)
Two hours before he vanished, Mark Dixon stole a glass of wine. That's what bartender Sophie Braam told the cops when they questioned her about the customer whose mutilated body was just found. What she didn't tell them is that she's the one who killed him. Officer Nora Martin is new to the Bellair Police Department and trying very hard to learn the ropes from Detective Murphy while ignoring all the men in the department snapping about a diversity hire. When she meets Sophie, they build an uneasy camaraderie over shared frustrations. As winter slides into spring and bodies start piling up, Nora begins to suspect that something's not quite right with the unnerving, enigmatic bartender. But will she be able to convince Murph, or will he keep laughing off the idea that the serial killer haunting their little town is a woman?